The Influence of Teacher Development on Secondary Content Area Supervision Among Preservice Teachers. Issue 1 (2nd January 2016) - Burbank, Mary D.; Bates, Alisa; Gupta, Udita
Abstract : This study addresses the issues and challenges faced by university supervisors when providing content-specific and general pedagogical feedback to preservice teachers. Study data highlight the perspectives of six preservice teachers as they reflect on their supervisory experiences over the course of a licensure year. Survey, interview, and written observation data from preservice teachers and university supervisors reveal the influence of teacher development and content area conventions on how preservice teachers view their teaching abilities and their expectations of university supervisors. Findings will inform how others may approach mentoring, support, and the evaluation of beginning teachers .